Love letters to a serial killer : [large type] a novel - Coryell, Tasha (Center Point Large Print, 2024)
"Recently ghosted and sick of watching her friends fade into the suburbs, thirty-something Hannah finds community in a true-crime forum that's on a mission to solve the murders of four women in Atlanta. After William, a handsome lawyer, is arrested for the killings, Hannah begins writing him letters. It's the perfect outlet for her pent-up frustration and rage. The exercise empowers her, and even feels healthy at first. Until William writes back. Hannah's interest in the case goes from curiosity to obsession, leaving space for nothing else as her life implodes around her. After she loses her job, she heads to Georgia to attend the trial and befriends other true-crime junkies like herself. When a fifth woman is discovered murdered, the jury has no choice but to find William not guilty, and Hannah is the first person he calls upon his release. The two of them quickly fall into a routine of domestic bliss. Well, as blissful as one can feel while secretly investigating their partner for serial murder . . ."--